La neumoconiosis : enfermedad profesional, su legislación en nuestro país y sus principales aspectos - Castillo Díaz, Pedro F. (1938)
They are so many and varied aspects and challenges to the subject of your erstudio pneumoconiosis, in all countries, worries researchers, clinicians, pathologists, radiologists, hygienists, engineers, entrepreneurs of large industries, the legislators and therefore the State.